Knowledge Preservation of Ondel-ondel as Icon of Jakarta - Bukhori, Farhan; Adriani-Salim, Tamara (UI Scholars Hub, 2018)
Ondel-ondel is a puppets become an icon pride city of Jakarta as a result of the community especially the Betawi culture as the original inhabitants of Jakarta. This paper attempts to reveal the icon Jakarta through the history, description, function and how to preserve the culture of local order not dragged down by the current modernization that progressively growing fast. This research uses qualitative methods and served proper techniques of descriptive obtained the Courtâ s website through the study of literature. Stage arts preservation ondel-ondel namely through stage screening, storage and actualization. The efforts to maintain and preserve the ondel-ondel as one of khazanah Indonesian culture is with: enter the subjects of genuine arts Jakarta especially Ondel-ondel into the educational curriculum, using ondel-ondel in each event of provincialism, change the puppet ondelondel regularly in the building of government and the culture of DKI Jakarta in order to preserve the craftsmen ondel-ondel, create sudios or betawi arts groups in each village, packs form of puppets ondel-ondel into the miniature or animation that preferred by the children as the successor of the cultural heritage.